Genetic Diversity of Kedu Chicken Based on Phenotypic Characteristics and Microsatellite Loci - Ismoyowati; Sukardi; Susanto, Agus (International Journal of Poultry Science, 2012)
This study was aimed to evaluate the genetic diversity based on phenotype and the genetic relationship between four kinds of Kedu chicken, using 4 microsatellite markers. The result from the phenotype observations showed that the four chicken breeds have qualitatively different plumage, skin, comb and shank colours. Cemani chickens’ have lower egg production than others. The results from the isolation and identification of DNA using microsatellite primers showed that the 4 primers were polymorphics. The highest polymorphic information contain values based on locus derived from the entire population was LEI 0147 (0.643), while the average polymorphic information contain value on each population were 0.362, 0.531, 0.482 and 0.568 for Cemani, white Kedu, red Kedu and black Kedu chickens, respectively. Estimation of the heterozygosity value on loci of different populations of Kedu chickens showed a large variation (0.618-0.743). Genetic distance analysis showed that among Kedu chickens had a genetic relationship ranging from 0.018 to 0.236. The conclusion was that the genetic diversity based on chicken phenotypes and based on microsatellite markers in the population of Kedu chickens indicated a high diversity and had a relatively distant genetic relationship.